2017
DOI: 10.1140/epjc/s10052-017-4938-y
|View full text |Cite
|
Sign up to set email alerts
|

The effective field theory of nonsingular cosmology: II

Abstract: Based on the effective field theory (EFT) of cosmological perturbations, we explicitly clarify the pathology in nonsingular cubic Galileon models and show how to cure it in EFT with new insights into this issue. With the least set of EFT operators that are capable to avoid instabilities in nonsingular cosmologies, we construct a nonsingular model dubbed the Genesis-inflation model, in which a slowly expanding phase (namely, Genesis) with increasing energy density is followed by slow-roll inflation. The spectru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 97 publications
(180 reference statements)
0
92
0
Order By: Relevance
“…The P (φ, X) nonsingular bounce model could be ghostfree [31,37], but suffers the problem of c 2 s < 0, which can not be dispelled by using the Galileon interaction ∼ φ [6][7][8][9]. Actually, in [10,38], it is observed that the Galileon interaction only moves the period of c 2 s < 0 to the outside of the bounce phase, but can not remove it, see also earlier [39]. Thus it could be imagined that the quadratic order of the second order derivative of φ, i.e., φ µν φ µν , ( φ) 2 , φ µ φ µρ φ ρν φ ν and ( φ)φ µ φ µν φ ν , might play crucial roles in stable nonsingular bounce model.…”
Section: Jhep09(2017)027 4 Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The P (φ, X) nonsingular bounce model could be ghostfree [31,37], but suffers the problem of c 2 s < 0, which can not be dispelled by using the Galileon interaction ∼ φ [6][7][8][9]. Actually, in [10,38], it is observed that the Galileon interaction only moves the period of c 2 s < 0 to the outside of the bounce phase, but can not remove it, see also earlier [39]. Thus it could be imagined that the quadratic order of the second order derivative of φ, i.e., φ µν φ µν , ( φ) 2 , φ µ φ µρ φ ρν φ ν and ( φ)φ µ φ µν φ ν , might play crucial roles in stable nonsingular bounce model.…”
Section: Jhep09(2017)027 4 Discussionmentioning
confidence: 99%
“…Recently, this observation has been proved, up to the cubic Galileon theory [6] and the Horndeski theory [7]. Based on the effective field theory (EFT) of nonsingular cosmologies [8][9][10], this No-go result has been more clearly illustrated. It is found that the stable nonsingular cosmological models can be implemented only in the theories beyond cubic Galileon, (see also [11,12]).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Recently, the EFT has also been applied to the nonsingular cosmologies [20][21] [22]. It was found first in Refs.…”
Section: Introductionmentioning
confidence: 99%